Analysis of Raw Material Inventory Control in the Mas Min Mie Pangsit Business in Tebeng, Bengkulu City - Try Saputra; Oni Yulianti; Ermy Wijaya (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2021)
The objective of the Economic Order Quantiity (EOQ) method in the Mie Pangsit Mas Min in Tebeng, Bengkulu City is to answer how to determine the right amount of inventory in the company so that the smooth production process is guaranteed without increasing storage costs and ordering costs. Data collection methods used in this study are EOQ (Economic Order Quantity), which is an analysis based on the calculation of the EOQ method as a basis or reference for determining the quantity of economical raw material orders. The result of this research is that according to company policy, the average purchase of wheat flour is 575 kg, while according to the EOQ method, the optimal purchase amount of starch is 158.1 kg. According to company policy the total inventory cost is Rp. 5,837,625, whereas calculated according to the EOQ method the total cost of inventory is Rp. 2,416,117. The frequency of the company's previous orders is 2 times the order in 6 months, whereas it is calculated by the EOQ method the more efficient ordering is 6 times the order in 6 months. The amount of safety stock required by Mas Min's dumpling noodle business is 158.1 kg. The re-order point that must be done by Mas Min's dumpling noodle business according to the EOQ method is when the raw materials are only 170,736 kg.